2018
DOI: 10.1111/1755-5922.12435
|View full text |Cite
|
Sign up to set email alerts
|

The reverse remodeling response to sacubitril/valsartan therapy in heart failure with reduced ejection fraction

Abstract: Switching therapy in eligible HFrEF patients from a RAS-blocker to sacubitril/valsartan induces beneficial reverse remodeling of both metrics of systolic as diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
110
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(148 citation statements)
references
References 30 publications
24
110
1
4
Order By: Relevance
“…Some studies have reported rates as low as 17%, and the majority of studies achieved the maximum dose in less than 50% of individuals . Given that emerging data indicate that the higher doses are associated with superior clinical response, close analyses of the impediments to dose titration in the community are warranted in order to provide guidance on how best this agent in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported rates as low as 17%, and the majority of studies achieved the maximum dose in less than 50% of individuals . Given that emerging data indicate that the higher doses are associated with superior clinical response, close analyses of the impediments to dose titration in the community are warranted in order to provide guidance on how best this agent in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its peculiar phenotype (tachycardia, low blood pressure, LV and/or right ventricular involvement, and dilated ventricles), intervention strategies may be challenging. 87 During the congress, the preliminary results of MADIT-CHIC Study (NCT02164721) by Singh et al 88,89 were also discussed. During the first year of follow-up, echocardiography was conducted every 3 months, then for another 4 years every 6 months, and after that once a year.…”
Section: Treatment Of Cardiotoxicity and New Frontiersmentioning
confidence: 99%
“…There is also a need to investigate the effects and possible benefits of sacubitril/valsartan for the treatment of CTRCM. 87 During the congress, the preliminary results of MADIT-CHIC Study (NCT02164721) by Singh et al 88,89 were also discussed. Thirty patients (87% female) with CTRCM and lymphoma or breast cancer, which qualified for cardiac resynchronizationdefibrillator therapy, participated in the trial.…”
Section: Treatment Of Cardiotoxicity and New Frontiersmentioning
confidence: 99%
“…Rather, indirect effects from other beneficial actions of the drug on the entire cardiovascular system might explain the association between diuretic dose changes and sacubitril/valsartan ( Figure ). Indeed, in a real‐world cohort, treatment with sacubitril/valsartan led to significant reverse remodelling of both metrics of systolic and diastolic left ventricular function, as well as a reduction in filling pressures and right ventricular systolic pressures . Of note, lower right ventricular systolic pressure has been shown to be significantly associated with success of loop diuretic down‐titration in patients with stable chronic heart failure .…”
mentioning
confidence: 99%
“…Indeed, in a real-world cohort, treatment with sacubitril/valsartan led to significant reverse remodelling of both metrics of systolic and diastolic left ventricular function, as well as a reduction in filling pressures and right ventricular systolic pressures. 11 Of note, lower right ventricular systolic pressure has been shown to be significantly associated with success of loop diuretic down-titration in patients with stable chronic heart failure. 12 Furthermore, sacubitril/valsartan improved symptoms and physical limitations of heart failure as assessed by the Kansas City Cardiomyopathy Questionnaire, with consistent improvements during follow-up.…”
mentioning
confidence: 99%